THE INFLUENCE OF MACHINE MAINTENANCE AND RAW MATERIAL INVENTORY ON THE SMOOTHNESS OF PRODUCTION PROCESSES AT PT INDOMETAL SEDJATI - Hananto, Djoko; Sudarman, Daman (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2024)
This study aims to test and analyze the effect of machine maintenance and raw material inventory on the smooth production process at PT. Indometal Sedjati. This study employs an associative research approach, utilizing a quantitative method. Data collection is done through a questionnaire, incorporating both primary and secondary data. The research population consists of 100 respondents, with a non-probability sampling technique being employed. Data analysis includes validity test analysis, reliability test, classic assumption test, multiple linear regression test, and hypothesis testing, utilizing SPSS Version 22 software. The results of this study indicate that partially machine maintenance has a positive and significant effect on the smooth running of the production process with a tvalue of 5.049 > 1.660 and a significance value of 0.000 <0.05, raw material inventory has a positive and significant effect on the smooth running of the production process with a tvalue of 5.006 > 1.660 and a significance value of 0.000 <0.05. In the F test, if the significant value is 0.000, then Ho is rejected and Ha is accepted. This indicates that machine maintenance and raw material inventory have a significant effect on the production process. The fvalue is 108.520, which is greater than 3.09, and the significant value is less than 0.05.